2011
DOI: 10.1089/hum.2010.202
|View full text |Cite
|
Sign up to set email alerts
|

Good Manufacturing Practice Production of Self-Complementary Serotype 8 Adeno-Associated Viral Vector for a Hemophilia B Clinical Trial

Abstract: To generate sufficient clinical-grade vector to support a phase I/II clinical trial of adeno-associated virus serotype 8 (AAV8)-mediated factor IX (FIX) gene transfer for hemophilia B, we have developed a large-scale, good manufacturing practice (GMP)-compatible method for vector production and purification. We used a 293T-based two-plasmid transient transfection system coupled with a three-column chromatography purification process to produce high-quality self-complementary AAV2/8 FIX clinical-grade vector. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 53 publications
2
142
1
Order By: Relevance
“…In many manufacturing procedures, these can constitute a majority of the initial product (Ͼ 90%). [29][30][31] Manufacturing processes vary in terms of whether these "empties" are removed or not. Evidence has accumulated, though, 32 to suggest that empty AAV capsids can gain access to a target cell and thus contribute to the intracellular capsid burden that will eventually be processed and presented on the surface of the transduced cell, flagging these cells for destruction by capsid-specific CD8 ϩ T cells.…”
Section: The Interplay Of Manufacturing Issues With Toxicities Relatementioning
confidence: 99%
“…In many manufacturing procedures, these can constitute a majority of the initial product (Ͼ 90%). [29][30][31] Manufacturing processes vary in terms of whether these "empties" are removed or not. Evidence has accumulated, though, 32 to suggest that empty AAV capsids can gain access to a target cell and thus contribute to the intracellular capsid burden that will eventually be processed and presented on the surface of the transduced cell, flagging these cells for destruction by capsid-specific CD8 ϩ T cells.…”
Section: The Interplay Of Manufacturing Issues With Toxicities Relatementioning
confidence: 99%
“…[35][36] AAV has been approved by the Food and Drug Administration as a vector for clinical gene therapy. [37][38][39][40][41][42][43][44] In this study we found that the virus had no effect on growth rate, food consumption (data not shown), or heart function. There were no deaths following the tail vein injection and the rats developed no abnormalities for the duration of the treatment.…”
Section: Discussionmentioning
confidence: 54%
“…AAV currently appears to be the safest human gene therapy vector for central nervous system clinical trials as it transduces nondividing cells without genomic integration, leading to long-term expression, and there are multiple different capsid variants available to improve cell-specific transduction [99]. Genes encoding intrabodies are small enough (750 nucleotides for scFvs and 360-420 for singledomain nanobodies) that the coding regions can be readily accommodated within either single or double-stranded AAV vectors [100], leaving space for bispecific or bifunctional constructs. A localized immune response to AAV9 that induced a response against the transgene was recently reported in rats [101].…”
Section: Next Directions In Gene Deliverymentioning
confidence: 99%